Strategy Kampanye Gerakan #BijakBerplastik PT Danone Aqua Dalam Merayakan Hari Lingkungan Hidup Sedunia 2018 - Siti Qonaah (Jurnal Komunikasi, 2019)
World Environment Day (WED) is the largest environmental preservation campaign in the world and commemorated on June 5, 2018 with the theme "Defeating Plastic Pollution". PT Danone Aqua on World Environment Day 2018 carried out the #BijakBerplastik movement campaign strategy by carrying out various activities in overcoming problems in the land and sea environment. The #BijakBerplastik movement carried out covers three main aspects that are important in dealing with plastic problems in Indonesia, namely: product innovation, consumer education, and the development of garbage collection infrastructure. This research is to find out the #BijakBerplastik  movement campaign strategy in celebrating world environmental day 2018. In this study researchers used a qualitative approach and case study, as a research method that illustrates the #BijakBerplastik movement campaign strategy through the latest launch of 100% Aqua bottle design is the result of a cycle re-exploring and recycling plastic waste in an event with the theme " Circularity Tour" can be useful in overcoming the problem of long-term environmental damage.